Pancreatic Stellate Cells and Metabolic Alteration: Physiology and Pathophysiology - Hamada, Shin; Matsumoto, Ryotaro; Masamune, Atsushi (Frontiers in Physiology, 2022)
Pancreatic stellate cells play a pivotal role in the development of pancreatic fibrosis. A wide variety of external stimuli can cause PSC activation accompanied by metabolic changes, which alters the tissue microenvironment by producing extracellular matrix proteins, cytokines, growth factors, and other mediators. Several metabolites aggravate fibrosis and inflammation by acting as key activating factors for PSCs. In other words, PSCs sense systemic metabolic changes. PSC activation alters intracellular metabolism and affects energy production. The detrimental effects of PSC activation on normal pancreatic cells, especially islet cells, further complicate metabolic imbalance through the dysregulation of glucose metabolism. PSC activation promotes cancer by altering the metabolism in pancreatic cancer cells, which collaborate with PSCs to efficiently adapt to environmental changes, promoting their growth and survival. This collaboration also contributes to the acquisition of chemoresistance. PSCs sequester chemotherapeutic agents and produce competing molecules as additional resistance mechanisms. The application of these metabolic targets for novel therapeutic strategies is currently being explored. Deciphering the complex regulation of metabolism propagated by various cell-to-cell interactions is indispensable for establishing radical therapies for pancreatic diseases. This mini review summarizes the role of PSCs in metabolic regulation of normal and cancerous cells.